Optimalisasi Pemasaran Digital Umkm Untuk Meningkatkan Penjualan Produk Lokal - Ahmad Faqih; Ahmad Rifa’i; Aulia Nur Rochmah; Azis Alma’as (CV. Multi Kreasi Media, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving both local and national economies. However, in today's digital era, many MSME players have not yet optimally utilized information technology, particularly in the field of marketing. The lack of digital skills and limited understanding of online promotional strategies have made local products less competitive and less recognized in wider markets. This Community Service Program (PKM) aims to enhance the digital marketing capacity of MSME players, especially in utilizing online platforms for promoting and selling local products. The program was carried out through a series of training sessions and direct mentoring with partner MSMEs, focusing on setting up business accounts on social media, using marketplaces, developing digital branding strategies, and creating engaging visual content. The tools used included Instagram Business, WhatsApp Business, Shopee, and design applications such as Canva. The training was delivered in a practical manner using case studies and hands-on simulations involving the participants' own products. Evaluation was conducted through pre-tests and post-tests, as well as observation of participants' digital activities after the training. The results showed a significant improvement in participants’ understanding of digital marketing. Most MSME partners successfully activated their business accounts, began posting product content regularly, and were able to design seasonal promotional strategies. In addition, participants demonstrated high enthusiasm to continue learning and growing their businesses digitally. This program has had a tangible impact in helping MSMEs reach wider markets and build stronger brand identities. Moving forward, this training can serve as a sustainable initiative as part of the comprehensive digital transformation of MSMEs.